Deteksi molekuler mecA pada isolat klinis methycilin resistant Staphylococcus aureus (MRSA) dengan menggunakan teknik polymerase chain reaction (PCR) di RSUP Sanglah Denpasar - Putu Ayu Utami Prajawaty; Ni Nengah Dwi Fatmawati (DiscoverSys Inc., 2018)
Introduction: MRSA is a bacteria that has experienced resistance to antibiotics, which generally has a function in killing Staphylococcus aureus, for the example Methicillin. In the worldwide MRSA prevalence is increasing, while the factors that cause the increase of the prevalence of MRSA is increasing the length of time of treatment in hospital, the misuse of antibiotics and poor infection control in the hospital. Laboratory tests were good and accurate were needed to identify MRSA as soon as possible so as to enable to conduct appropriate infection control. The aim of this study was to determine that the PCR can be used to confirm MRSA isolates.Methods: This study used a cross sectional design on all isolated Staphylococcus aureus isolates from all clinical specimens examined at the Laboratory of Clinical Microbiology, Sanglah General Hospital, Denpasar from 2011 until 2012.Results: A total of 38 samples were used, 32 (84.2%) positive S. aureus confirmed mecA genes using PCR technique. However, there are still 15.8% who are misidentified, where the possibility of the bacteria is not MRSA or the retrieval technique from the bacteria itself when conducting the research.Conclusion: MecA gene examination using PCR method is an examination that can be used to detect MRSA bacteria.Â